1991
DOI: 10.1104/pp.95.2.570
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a UDPGlucose: Flavonol O3-Glucosyltransferase from Illuminated Red Cabbage (Brassica oleracea cv Red Danish) Seedlings

Abstract: A UDPGlc:flavonol 03-glucosyltransferase (EC 2.4.1.91) that catalyzes the formation of quercetin and kaempferol 03-glucosides has been purified about 1450-fold from illuminated red cabbage (Brassica oleracea cv Red Danish) seedlings with a 3.3% yield. Purification of the enzyme was achieved by (NH4)2SO4-precipitation, gel-filtration, ion-exchange chromatography on DEAE-Bio-Gel and Q-Sepharose, chromatofocusing, and electrophoresis in nondenaturing polyacrylamide (10%) gels. The enzyme preparation had a pH opfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Isoelectric focusing indicated that the CGTase had a pI of 5.0. Other plant GTases associated 11 with secondary metabolism also have molecular masses of 40-62 kDa [17], consist of a single subunit or are dimers of subunits of 20-32 kDa, and have a pI near 5.0 [5,7,[19][20][21]. Thus, the physical characteristics of the CGTase were similar to those of other plant GTases.…”
Section: Physical Propertiesmentioning
confidence: 87%
“…Isoelectric focusing indicated that the CGTase had a pI of 5.0. Other plant GTases associated 11 with secondary metabolism also have molecular masses of 40-62 kDa [17], consist of a single subunit or are dimers of subunits of 20-32 kDa, and have a pI near 5.0 [5,7,[19][20][21]. Thus, the physical characteristics of the CGTase were similar to those of other plant GTases.…”
Section: Physical Propertiesmentioning
confidence: 87%
“…For example, quercetin glycosides, such as rutin (quercetin 3-rutinoside), have a cyanidin glycosides-like structure and are among the main flavonoids in citrus leaves (Kawaii et al 2000). UFGTs from red cabbage seedlings and apple are able to use quercetin more efficiently than cyanidin as a substrate (Sun and Hrazdina 1991;Ju et al 1995). Recently, Offen et al (2006) showed that red grape UFGT (VvGT1), responsible for the formation of anthocyanins, is active, in vitro, on a range of flavonoids.…”
Section: Discussionmentioning
confidence: 98%
“…The ability to separate S-GT from this widely occurring flavonol glucosyltransferase activity (Sun and Hrazdina, 1991) provides further evidence that S-GT is specific for thiohydroximates. The enzyme does not act on oxygen analogs of hydroximates (Reed et al, 1993).…”
Section: Enzyme Specificity and Occurrencementioning
confidence: 94%